Hydrochlorothiazide Induced Lichen Planus in the Emergency Department: A Case Report. (April 2017) - Sin, Billy; Miller, Morgan; Chew, Edward
Lichen planus (LP) is a mucocutaneous inflammatory disease that involves papulosquamous eruption of the skin, scalp, nails, and mucous membranes. This uncommon condition has a higher prevalence in African Americans and females. Women accounts for 50% of cutaneous LP (CLP) and 60% to 75% of oral LP (OLP) cases. Diagnosis is centered around clinical presentation. Patient evaluation requires a comprehensive physical examination to identify any potential sites of involvement. LP is usually described by the "Six P's": planar, purple, polygonal, pruritic, papules, and plaques. Drug-induced LP, or lichenoid drug reactions, is uncommon and usually indiscernible from other forms of LP. Lichenoid drug reactions exhibit parakeratosis, dermal infiltrates of eosinophils, or perivascular lymphocytic infiltrates affecting the reticular dermis. An extended time interval between the initiation of drug to the onset of symptoms usually does not exclude potential diagnosis of a lichenoid drug reaction. We describe a case of hydrochlorothiazide-induced LP without prolonged exposure to sunlight diagnosed in the emergency department (ED). In this case, a pharmacist-conducted medication reconciliation played an integral role in accurately recognizing this adverse drug reaction. Our case report adds to the limited available literature on the topic, most of which originated more than 30 years ago.